Effect of general warm-up plus dynamic stretching on endurance running performance in well-trained male runners - Yamaguchi, T.; Takizawa, K.; Shibata, K.; Tomabechi, N.; Samukawa, M.; Yamanaka, M. (Research Quarterly for Exercise and Sport, 2019)
Purpose: The purpose of this study was to compare the acute effects of general warm-up (GWU) and GWU plus dynamic stretching (GWU + DS) on endurance running performance in well-trained male runners. Method: The endurance running performances of eight well-trained long-distance male runners were assessed on a treadmill after 2 types of intervention for 5 min after running on the treadmill at a velocity equivalent to 70% maximal oxygen uptake (VO2max) in each athlete for 15 min. The interventions were GWU and GWU + DS. In the GWU + DS intervention, dynamic stretching was performed for ten repetitions as quickly as possible for the five muscle groups of the lower extremities. The total duration of the dynamic stretching was 3 min and 45 s. Endurance running performance was assessed at 1 min 15 s after the dynamic stretching. The endurance running performance was evaluated by the time to exhaustion (TTE) during running at a velocity equivalent to 90% VO2max in each athlete. Results: The TTE (640.6 ± 220.4 s) after GWU + DS intervention was significantly (d = 1.02, p = .03) shorter than that (760.6 ± 249.1 s) after GWU intervention. Conclusions: The results demonstrated that GWU + DS intervention impaired immediate endurance performance of running at a velocity equivalent to 90% VO2max in well-trained male runners compared with GWU intervention. Thus, we are not able to recommend that well-trained runners and their coaches use the protocol for GWU + DS described in this study during actual warm-ups.